Propriedades físico-hídricas, desenvolvimento radicular e produtividade da soja em dois tipos de manejos de solo - de Aguiar e Silva, Marcelo Augusto (2012)
The soybean culture is part of crop rotation used by irrigators from the southwestern region of São Paulo State that perform no-tillage soil management as a form of sustainable soil use. The objective of this work was to evaluate the effect of this conservationist practice on physicalhydric properties, soil compaction, root development, and soybean culture production components in relation to the conventional management. The experiment was conducted at the Buriti-Mirim Farm, Angatuba, SP, in Brazil, using an area irrigated by a center pivot system divided into two types of soil management: conventional and no-tillage. Although the no-tillage management presented higher soil density, lower water available and lower soil resistance to penetration, both soil managements showed no difference in relation to root development.